2021
DOI: 10.3389/fimmu.2021.626755
|View full text |Cite
|
Sign up to set email alerts
|

MSCs and Inflammatory Cells Crosstalk in Regenerative Medicine: Concerted Actions for Optimized Resolution Driven by Energy Metabolism

Abstract: Mesenchymal stromal cells (MSCs) are currently widely used in cell based therapy regarding to their remarkable efficacy in controlling the inflammatory status in patients. Despite recent progress and encouraging results, inconstant therapeutic benefits are reported suggesting that significant breakthroughs in the understanding of MSCs immunomodulatory mechanisms of action remains to be investigated and certainly apprehended from original point of view. This review will focus on the recent findings regarding MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 215 publications
(212 reference statements)
1
55
0
Order By: Relevance
“…MSCs directly target the Th-17 cells and increase their expression of FoxP3 mRNA, thus switching them into Tregs and inhibiting their production of inflammatory cytokines. MSCs can also inhibit the Th1-driven autoimmune response (196)(197)(198). The effect of donor MSCs on the recipient is mainly through paracrine release of various cytokines (199), which not only participate in the regulation of immune response but also promote tissue repair (178).…”
Section: Mscs Transplantationmentioning
confidence: 99%
“…MSCs directly target the Th-17 cells and increase their expression of FoxP3 mRNA, thus switching them into Tregs and inhibiting their production of inflammatory cytokines. MSCs can also inhibit the Th1-driven autoimmune response (196)(197)(198). The effect of donor MSCs on the recipient is mainly through paracrine release of various cytokines (199), which not only participate in the regulation of immune response but also promote tissue repair (178).…”
Section: Mscs Transplantationmentioning
confidence: 99%
“…At the cellular level, the BMSC pool in the BM niche shows a biased differentiation towards adipogenesis at the cost of osteoblastogenesis in aging ( 48 ). Despite their regenerative capabilities, BMSCs were shown to have decreased differentiation potential when exposed to inflammatory environments ( 49 ). Josephson et al.…”
Section: The Effects Of Bma On Bone Marrow Stromal Cells and Hematopo...mentioning
confidence: 99%
“…Interleukin-10, also associated with the expression of ASPS, IGF1 and its receptor IRS-1, clearly has chondroprotection activity, stimulating the expression of collagen type II and proteoglycan and regulating the maintenance of tissue integrity [ 48 ]. Moreover, our results demonstrated that adipose tissue also hosts chemokines such as 11β-HSD1, PPARγ, and adiponectin which have been shown to contribute to immunoregulation through modulation of hMSC metabolism [ 49 , 50 ], but also chemokines such as MCP1, Visfatin, and Resistin which have been shown to contribute to immunoregulation through modulation of macrophages plasticity [ 51 ]. Beyond that, adiponectin, ASPS, MCP1, Visfatin, and Resistin, when taken together, prove that they can contribute to the diagnosis of OA, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%